Enforcing the European Semester: the politics of asymmetric information in the excessive deficit and macroeconomic imbalance procedures. Issue 2 (1st February 2018) - Savage, James D.; Howarth, David
ABSTRACT: The European Semester is an information-driven surveillance system that relies upon budgetary and economic statistics collected from the European Union's memberstates and analyzed by the European Commission. This is true for both the Excessive Deficit Procedure (EDP) and the Macroeconomic Imbalance Procedure (MIP). This article employs Principal–Agent theory to analyze the politics of asymmetric information in the EDP and MIP. The study explores how the statistical requirements of the Six-Pack have been enforced by the Commission and the Economic and Financial Affairs Council to strengthen the EDP, even as the statistical integrity of the MIP received less protection. The article examines how the misrepresentation of statistics by Spain's Autonomous Community of Valencia provoked the first financial sanction in the history of Economic and Monetary Union, as well as the Commission's unsuccessful efforts to strengthen the reliability of MIP statistics.